Re-conceiving Liberal Education: The Philosophical Route Less Taken in the Confused and Confusing Contemporary Society - Servaña, Alvin (Journal of Education and Learning Environments, 2025)
This essay presents a critical philosophical examination of contemporary educational realities within the Southeast Asian context, particularly focusing on the Philippines and broader ASEAN region. Employing Presuppositional Epistemology—the principle that knowledge emerges from foundational commitments and principles—this study argues that education is never theologically or morally neutral, necessitating rigorous philosophical inquiry into educational practice. The paper addresses the pervasive learning crisis evidenced by recent data showing that nine out of ten Filipino children aged ten cannot read simple texts, alongside declining enrollment rates across the region. Through systematic metaphysical analysis of learners, educators, and institutional frameworks, this treatise challenges prevailing educational paradigms that prioritize economic utility over human flourishing. The methodology integrates classical philosophical inquiry with contemporary educational criticism, examining how ignorance—conceptualized as a noetic effect of human depravity—manifests in systemic educational failures across ASEAN nations. The study proposes a reconceptualized philosophy of education that synthesizes Essentialist rigor, Perennialist wisdom, Existentialist authenticity, and Critical Pedagogical liberation, offering a holistic response to the educational crises plaguing Southeast Asian societies. This philosophical framework contends that authentic education must confront competing worldviews while maintaining an unwavering commitment to truth, wisdom, and human dignity in an increasingly fragmented global landscape.